2018
DOI: 10.4012/dmj.2016-418
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblastic differentiating potential of dental pulp stem cells <i>in vitro</i> cultured on a chemically modified microrough titanium surface

Abstract: Titanium surface modification is critical for dental implant success. Our aim was to determine surfaces influence on dental pulp stem cells (DPSCs) viability and differentiation. Implants were divided into sandblasted/acid-etched (control) and sandblasted/acid-etched coated with calcium and magnesium ions (CaMg), supplied as composite, (test). Proliferation was evaluated by MTT, differentiation checking osteoblastic gene expression, PGE2 secretion and matrix formation, inflammation by Interleukin 6 (IL-6) dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Several studies demonstrated that surface modifications in dental implants are able to further ameliorate their integration process into the host bone tissue. In particular, a previous study performed in our laboratory demonstrated that a sandblasted and acid-etched surface further treated with inorganic ions guarantees an improvement in cell viability, a low inflammatory response, a faster promotion of the osteoblastic differentiation, a higher biocompatibility, and a better tolerability by both human osteoblasts and DPSCs, compared to a simply sandblasted and acid-etched titanium surface [6,7]. For this reason, we decided to compare, in the present study, only machined, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies demonstrated that surface modifications in dental implants are able to further ameliorate their integration process into the host bone tissue. In particular, a previous study performed in our laboratory demonstrated that a sandblasted and acid-etched surface further treated with inorganic ions guarantees an improvement in cell viability, a low inflammatory response, a faster promotion of the osteoblastic differentiation, a higher biocompatibility, and a better tolerability by both human osteoblasts and DPSCs, compared to a simply sandblasted and acid-etched titanium surface [6,7]. For this reason, we decided to compare, in the present study, only machined, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Only impacted teeth without dental pathologies were included in the study. After the extraction, all the remaining soft tissues were mechanically removed and processed, as reported in our previous work [7].…”
Section: Isolation and Cultivation Of Dpscsmentioning
confidence: 99%
See 2 more Smart Citations
“…When hDPSCs are seeded on porous surfaces they show osteoblast differentiation, production of appreciable amounts of bone morphogenetic proteins as well as vascular endothelial growth factor and specific bone proteins (Perrotti et al, 2013). Recent work suggests that chemically modified microrough titanium surfaces are more osteoinductive, which represents a significant advantage for application in the dental clinic (Boyan et al, 2018;DE Colli et al, 2018). In the present study a small but significant difference in the levels of expression of OSTERIX was found, when comparing Ti6Al4V (smooth) and BAS (rough biomimetic) surface-grown hDPSCs in control (no osteoblastic stimulation) conditions.…”
Section: Discussionmentioning
confidence: 99%